2019
DOI: 10.1002/ptr.6403
|View full text |Cite
|
Sign up to set email alerts
|

A review of molecular mechanisms involved in anticancer and antiangiogenic effects of natural polyphenolic compounds

Abstract: The aim of this review is to obtain a further understanding of the reported inhibitory effects of polyphenols on cancer cell proliferation and angiogenesis process and the probable mechanisms by which these natural compounds inhibit proliferation of cancer cells and angiogenesis. Growing evidence indicates that polyphenols are beneficial against human fatal diseases such as cancer. Because angiogenesis has a critical role in tumor growth and metastasis, therefore, we decided to review the potential anticancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 122 publications
(149 reference statements)
0
47
0
Order By: Relevance
“…Silibinin is a polyphenolic flavonolignan of slymarin from seeds of milk thistle (Silybum marianum) and multitude published reports proved different anticancer efficacy of silibinin in experimental in vitro and in vivo models. These anticancer properties include apoptosis induction, inhibiting cell proliferation, angiogenesis, and inhibition of invasion in a variety of cancer models [12][13][14]. Silibinin has been revealed to be an effective chemotherapeutic and chemopreventive agent without unwanted side effects and therefore it could have potential clinical application for breast cancer treatment [15].…”
Section: Resultsmentioning
confidence: 99%
“…Silibinin is a polyphenolic flavonolignan of slymarin from seeds of milk thistle (Silybum marianum) and multitude published reports proved different anticancer efficacy of silibinin in experimental in vitro and in vivo models. These anticancer properties include apoptosis induction, inhibiting cell proliferation, angiogenesis, and inhibition of invasion in a variety of cancer models [12][13][14]. Silibinin has been revealed to be an effective chemotherapeutic and chemopreventive agent without unwanted side effects and therefore it could have potential clinical application for breast cancer treatment [15].…”
Section: Resultsmentioning
confidence: 99%
“…The pattern of the primary molecular structure of flavonoids, as well as the substitution of chemical groups in the flavonoid structure, is correlated with their human biological activity and bioavailability (Durazzo et al, 2019). In addition, flavonoids are the most abundant polyphenols in our diet according to Abbaszadeh et al (2019). At the same time, human epidemiological studies have demonstrated the potential impacts of dietary polyphenols on prevention of many cancer types (Pandey et al, 2009, Li et al, 2015, Wu et al, 2016, and the overall results from basic science research mostly agree with the potential role of flavonoids in the human diet as protective compounds (Grosso et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, epidemiological studies indicated that soybean-based diets may decrease cancer risk (Dong e al., 2011;Yan et al, 2009). Furthermore, Phase I/II clinical trials showed the potential efficacy of this isoflavone as an antimetastatic agent against prostate cancer (Pavese et al, 2014;Abbaszadeh et al, 2019).…”
Section: Isoflavonesmentioning
confidence: 99%
“…Free radical species have been reported to interfere with metabolic processes which lead to various chronic diseases [ 30 , 31 ]. Antioxidants such as phenolics play a crucial role in inhibiting oxidative stress and show a positive association with human health by strengthening immune defenses [ 32 , 33 ]. The antioxidant activity of plants can be determined by using different bioassays such as 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azino-bis(3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS) [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%